Expletive ta in Mandarin Chinese: A Quantitative Study - Yue Yu; Qiurong Zhao (Complexity)
Expletive pronouns have posed significant challenges to both linguistic studies and natural language processing in Chinese. Based on the data from the Chinese corpus at the Center for Chinese Linguistics of Peking University (CCL), this paper investigates the automatic dependency parsing errors of expletive ta (“it/he”) and relative constructions and provides a detailed quantitative analysis of the characteristics of the constructions in question. The findings not only provide evidence to show that even in radical pro-drop languages such as Mandarin, pleonastics can occur in both object and subject positions but also offer important insights for Chinese natural language processing.